Geometric modeling of the number of full-scale experiments for a 3-component material - Nurmakhanov B.N., Нурмаханов Б.Н.; Bektibaeva Z.K. , Бектыбаева З.К. (Рroblems of engineering and professional education, 2022)
In this paper, a geometric simulation of the experiment plan is considered, which makes it possible to reduce the number of full-scale experiments for the three-component composition.